Accuracy of the electronic patient record in a first opinion veterinary practice - Jones-Diette, Julie; Robinson, N.J.; Cobb, Malcolm; Brennan, Marnie L.; Dean, Rachel S. (Elsevier, 2017)
The use of electronic patient records (EPRs) in veterinary research is becoming more common place. To date no-one has investigated how accurately and completely they represent the clinical interactions that happen between veterinary professionals, and their clients and patients. The aim of this study was to compare data extracted from consultations within EPRs with data gathered by direct observation of the same consultation. A secondary aim was to establish the inter-rater reliability of two researchers who examined the data extracted from the EPRs. A convenience sample of 36 small animal consultations undertaken by 2 veterinary surgeons (83% by one veterinary surgeon) at a mixed veterinary practice in the United Kingdom was studied. All 36 consultations were observed by a single researcher using a standardised data collection tool. The information recorded in the EPRs was extracted from the Practice Management Software (PMS) systems using a validated XML schema. The XML extracted data was then converted into the same format as the observed data by two independent researchers who examined the extracted information and recorded their findings using the same tool as for the observation. The issues discussed and any action taken relating to those problems recorded in the observed and extracted datasets were then compared. In addition the inter-rater reliability of the two researchers who examined the extracted data was assessed. Only 64.4% of the observed problems discussed during the consultations were recorded in the EPR. The type of problem, who raised the problem and at what point in the consultation the problem was raised significantly affected whether the problem was recorded or not in the EPR. Only 58.3% of observed actions taken during the consultations were recorded in the EPR and the type of action significantly affected whether it would be recorded or not. There was moderate agreement between the two researchers who examined the extracted data. This is the first study that examines how much of the activity that occurs in small animal consultations is recorded in the EPR. Understanding the completeness, reliability and validity of EPRs is vital if they are to continue to be used for clinical research and the results to direct clinical care.